Effectiveness of Chlorella sp. in phytoremediation of different wastewater in North Aceh - Rachmawati Rusydi; Mahdaliana Mahdaliana; Isra Ambia; Muliani Muliani; Prama Hartami (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
Chlorella  sp. is microalgae species used to treat wastewater and can grow and develop well inside contaminated environments by interweaving symbiosis with bacterial decomposers. This study purposed to evaluate the effectiveness of Chlorella sp. in the phytoremediation of different wastewater from North Aceh. This research used the experimental laboratory method with an experimental design Non-Factorial Completely Randomized Design. The treatment factor was different wastewater obtained from North Aceh consisting of A: domestic wastewater, B: tofu wastewater, and C: slaughterhouse wastewater repeated three times. The observed parameters were water quality parameters (temperature, pH, dissolved oxygen, biological oxygen demand, nitrate, and phosphate concentration, decrement of organic materials, and microalgae growth. The result showed that Chlorella sp. could remediate the wastewater by decreasing the organic materials in the wastewater. The temperature, pH, and dissolved oxygen in wastewater were optimal for Chlorella’s life. Implementation of Chlorella sp. gave a significant effect (p<0.05) on the efficiency of organic materials decrement in wastewater, namely BOD 64,6%-65%, nitrate 76,8%-91,2%, and phosphate 72,7%-94,6%. Furthermore, the suitable wastewater for Chlorella sp. growth with its highest peak value (p<0,05) was the slaughterhouse wastewater. The recommended wastewater was slaughterhouse remediated by Chlorella sp. to be used as cultivation media of fish.